2015
DOI: 10.1021/la504923j
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid Composition Modulates Carbon Nanodiamond-Induced Alterations in Phospholipid Domain Formation

Abstract: The focus of this work is to elucidate how phospholipid composition can modulate lipid nanoparticle interactions in phospholipid monolayer systems. We report on alterations in lipid domain formation induced by anionically engineered carbon nanodiamonds (ECNs) as a function of lipid headgroup charge and alkyl chain saturation. Using surface pressure vs area isotherms, monolayer compressibility, and fluorescence microscopy, we found that anionic ECNs induced domain shape alterations in zwitterionic phosphatidylc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…Anionic diamond NPs can alter the packing and shape of ordered gel domains. 20 Positively-charged dendrimers and polymeric NPs have been shown to selectively disrupt the liquid phase of the bilayer over the gel phase. 21,22 Amphiphilic dendrimers have been shown to interact distinctly with bilayers of different phasesinducing partial solubilization of fluid bilayers, lipid patches and local depressions in gel bilayers, and a ribbon-like network with spherical aggregates in bilayers with both fluid and gel phases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anionic diamond NPs can alter the packing and shape of ordered gel domains. 20 Positively-charged dendrimers and polymeric NPs have been shown to selectively disrupt the liquid phase of the bilayer over the gel phase. 21,22 Amphiphilic dendrimers have been shown to interact distinctly with bilayers of different phasesinducing partial solubilization of fluid bilayers, lipid patches and local depressions in gel bilayers, and a ribbon-like network with spherical aggregates in bilayers with both fluid and gel phases.…”
Section: Introductionmentioning
confidence: 99%
“…21,22,25 Fluorescence microscopy has also been used to examine interactions between NPs and phase-segregated model membranes. 20,24,27 While not attaining the resolution of AFM, fluorescence microscopy provides high detection selectivity enabled by fluorescence tagging. 28 Correlative AFM and fluorescence microscopy can localize NPs in relation to other fluorescently tagged biomolecules with very high spatial resolution and detection selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Further, some of us have also previously shown that SP-B causes an increase in the line tension of a clinical lung surfactant, an important biophysical property of phospholipid films at the air–water interface, which can control the overall energy of the lipid films [29]. By correlating high resolution atomic force microscopy (AFM) images to calculations of line tension changes in different binary lipid films, we have also recently shown that a change in line energy can be directly related to the tendency of a molecule to act as a line active species [31]. Further, previous research by McConnel and co-workers has established the line tension lowering ability of cholesterol [32].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in addition to the surface pressure-area isotherms, the surface morphology should be carefully studied while assessing the behavior of the nanoparticles. Similarly, previous work from our lab has shown that the actual composition of the lipid mixture used can also lead to differences in interactions with nanoparticles [22]. However, the impact of nanoparticles on collapse mechanism in phospholipid monolayers is currently not well understood and has not been studied in detail.…”
Section: Introductionmentioning
confidence: 96%
“…Studies have shown that the chemistry of the surfactant mixtures (phospholipid combinations and presence of LS proteins or their synthetic analogs) enable fold formation during compression and reincorporation of material during expansion cycles [23][24][25]. On the other hand, our previous work, focused on ECN induced changes in lipid domain packing in the LE-LC regions has shown that differences in lipid-ECN interactions are modulated by other lipid headgroup charge and tail saturation [22]. Specifically, we observed that at lower surface pressures, the anionic ECNs behave as line active species when interacting with zwitterionic phospholipids.…”
Section: Introductionmentioning
confidence: 99%